PENGARUH FAKTOR GEOGRAFIS DAN DEMOGRAFIS DALAM KEPUTUSAN PEMBELIAN (STUDI KASUS PADA KONSUMEN UMKM DI KAWASAN WISATA PANTAI KOTA BENGKULU) - Tedy Sunardi; Fikri, Muhammad (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
This research aims to determine the influence of geographic and demographic factors in purchasing decisions (case study of MSME consumers in the coastal tourism area of ​​Bengkulu City). This research uses a quantitative approach with research methods based on the philosophy of positivism. The population used in this research was MSME consumers in the Long Beach tourist area of ​​Bengkulu City. Respondents were selected using a purposive sampling technique with a sample size of 130 people. Data was collected through a validated and reliable questionnaire. The data analysis technique used is multiple regression to test the hypothesis. The test results show that geographical factors (t_count = 3.018, Sig = 0.003) and demographic factors (t_count = 5.688, Sig = 0.000) have a positive and significant effect on individual purchasing decisions. Simultaneously, these two factors together have a significant influence on purchasing decisions (F_count = 28.354, Sig = 0.000).